’Hug Helps’ – Kindergarten Experiences Through the Eyes of Children at Risk of Social Exclusion - Visković, Ivana; Višnjić‑Jevtić, Adrijana (Journal of Qualitative Research in Education, 2025)
This study explores the perspectives of children at risk of social exclusion (RSE) regarding their everyday experiences in kindergarten. Using semi-structured, developmentally appropriate interviews, we examined the views of 48 children (M = 70.32 months) identified by teachers as vulnerable due to social, emotional, or contextual circumstances. Overall, children described kindergarten as a generally positive and enjoyable environment, emphasizing friendships, play, and familiar routines. However, many also expressed concerns related to limited autonomy and agency. Rules were frequently perceived as restrictive rather than supportive, and penalties often involved social or physical constraints, such as exclusion from activities or temporary isolation. Children also reported difficulties identifying consistent encouragement or available support from teachers, except during moments involving strong emotional distress. These findings highlight the ongoing need for inclusive, responsive, and autonomy-supportive pedagogical practices in early childhood education. The results suggest that children not only desire opportunities for participation but also need to feel visible, recognized, and respected as legitimate contributors to the educational process. Such reflections indirectly point to possible gaps in the quality of educational practice and the professional competencies of educators. Adults’ assumptions about knowing what is best for children may unintentionally restrict children’s participatory rights, particularly for those already at risk of social exclusion, who may have fewer opportunities to influence their learning environment.